Utilization of Canva in Improving Writing Procedure Text of Typical Cianjur Food in Class VII Students MTs Al-Mu’awanah Cianjur - Salma, Zihan; Adawiyah, Aprilla; Hasanah, Aan (Raja Zulkarnain Education Foundation, 2025)
This study aims to improve knowledge of language rules and structures in procedural texts with the theme of Cianjur's typical food. The study was conducted in the odd semester of 2024/2025 at MTs Al-Mu'awanah Cianjur. This study uses a One-Group Pretest-Posttest Design. The population of this study was 33 students of class VII-B MTs Al-Mu'awanah Cianjur. The sample was determined as many as 31 students randomly selected using a simple technique without replacement. A test instrument was used to collect data on the use of Canva in learning procedural text skills. This instrument is valid because it is arranged objectively and systematically and is used on two occasions, namely before learning activities and after learning activities using Canva. Data were analyzed using parametric inferential statistical procedures. The analysis results data were validated internally using a checklist with time triangulation techniques. The results of this study indicate that students experienced an increased knowledge of structure and language rules in writing procedural texts. This can be seen from the students' scores on the pretest and posttest results. There is a difference in the scores from the two tests, which shows an increase. Also, using Canva with infographic design is efficacious in improving the ability to write procedural texts on Cianjur's typical food for class VII-B students of MTs Al-Mu'awanah Cianjur. Therefore, Canva can be a learning medium to improve students' ability to write procedural texts on Cianjur's typical food.